Performance improvement strategies of CuWO4 photocatalyst for hydrogen generation and pollutant degradation. Issue 5 (October 2020) - Raizada, Pankaj; Sharma, Sonali; Kumar, Abhinandan; Singh, Pardeep; Parwaz Khan, Aftab Aslam; Asiri, Abdullah M.
Graphical abstract: Highlights: Potential of CuWO4 as a photocatalyst is explored. Various strategies to enhance photocatalytic performance are discussed. Photocatalytic applications of CuWO4 are summarized. Current challenges and potential solutions for future research are proposed. Abstract: Recently, photocatalysis has attracted all-embracing attention as a sustainable and green approach owing to its promising applications in the deterioration of contaminants along with the transformation of solar energy into chemical energy. An efficient visible-light harnessing Copper tungstate photocatalyst has hooked excellent performance because of its peculiar features, including eco-friendliness, low cost, optimum band edge potentials, as well as stability under oxidative and acidic conditions. However, any review depicting the correlation between different morphologies, properties, and performance of CuWO4 is still absent. Therefore, this review highlighted the energy applications of CuWO4 photocatalyst, focusing on its morphological dimensions and strategies for photocatalytic performance enhancement. Various fabrication methods, such as hydrothermal, electrodeposition, spray-pyrolysis, co-precipitation, sonochemistry, and solid-state synthesis, are also discussed. Controllable synthesis of distinct morphological nanostructures with the effect of parameters like temperature, pH, solvent, reaction time, and concentration of precursors has been briefly summarized. Nano-structured CuWO4 was explored to show high photocatalytic activity than pristine CuWO4 . Moreover, different revamp strategies, including doping of parent photocatalyst, loading of co-catalyst on photocatalyst surface, and heterojunction construction, are assumed for the efficient space charge isolation of photo charge carriers suppressing the rapid recombination of photo-generated electron-hole pairs for dynamic photocatalytic activity. The applications of CuWO4, including photocatalytic water reduction for H2 generation, photodegradation of dyes and antibiotics, and photoelectrochemical water splitting, have been highlighted. Finally, a brief, conclusive remark regarding present studies and unresolved challenges of nano-structured CuWO4 are put forth for future perspectives.